2020
DOI: 10.3389/fnins.2020.00474
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Microstructural Alterations Correlate With the Cognitive Performance of Rats: A Longitudinal in vivo Diffusion Tensor Imaging Study

Abstract: Background: Stress-induced cellular changes in limbic brain structures contribute to the development of various psychopathologies. In vivo detection of these microstructural changes may help us to develop objective biomarkers for psychiatric disorders. Diffusion tensor imaging (DTI) is an advanced neuroimaging technique that enables the non-invasive examination of white matter integrity and provides insights into the microstructure of pathways connecting brain areas. Objective: Our aim was to examine the tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 112 publications
(147 reference statements)
1
6
0
Order By: Relevance
“…However, the DTI and DKI results are less clear-cut. Microstructural disruption in WM, axonal degeneration, and demyelination in depression are generally believed to produce higher RD and MD and lower FA in both patients with depression ( 11 , 59 , 60 , 61 ) and animal models of depression ( 62 , 63 ), such as the Wistar–Kyoto strain genetic model ( 14 ) and chronic unpredicted mild stress model ( 13 ). Keeping in mind that relating DTI and DKI measures to tissue microstructure is difficult, our observation of higher FA values being driven by a decrease in RD and MD contradicts the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the DTI and DKI results are less clear-cut. Microstructural disruption in WM, axonal degeneration, and demyelination in depression are generally believed to produce higher RD and MD and lower FA in both patients with depression ( 11 , 59 , 60 , 61 ) and animal models of depression ( 62 , 63 ), such as the Wistar–Kyoto strain genetic model ( 14 ) and chronic unpredicted mild stress model ( 13 ). Keeping in mind that relating DTI and DKI measures to tissue microstructure is difficult, our observation of higher FA values being driven by a decrease in RD and MD contradicts the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also evaluated the relationship between measurements of stress and measurements of brain structure such as grey matter volume and white matter integrity with differing findings. In an animal model, stress has been associated with reduced FA in the corpus callosum and external capsule (Nagy et al, 2020) but there were no such findings in another study (Henckens et al, 2015). Some studies in humans showed that clinically severe stress such as a diagnosis of PTSD in adolescents with history of childhood adverse events was associated with lower FA in white matter tracts (Huang, Gundapuneedi, & Rao, 2012) although whether stress experienced by an otherwise healthy population would have a substantial effect on white matter is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…53 After intracerebral hemorrhage, hemoglobin changes from oxyhemoglobin to deoxyhemoglobin and hemosiderin and iron are released, which can be detected by MRI. 54 It has been found that cognitive impairments in stressed rats correlate with various DTI metrics of the corpus callosum and amygdala, 55 and experienceinduced differences in white matter and grey matter structures have also been observed by DTI in adult rats. 56 In this study, we first used DTI to evaluate the different brain regions after hemorrhage.…”
Section: Discussionmentioning
confidence: 99%